Checklist of Basidiomycota and New Records from the Azores Archipelago - Martin Souto; Pedro Miguel Raposeiro; Ana Balibrea; Vítor Gonçalves (Diversity, 2024)
This paper presents an annotated checklist of the Basidiomycota taxa (including lichenicolous fungi and the subdivision Pucciniomycotina) from the Azores archipelago and reviews the published records to account for their taxonomic status. The number of Basidiomycota species recorded in the Azores has increased considerably during the 20th century and now stands at 544 species. This study provides distribution data and includes changes in the nomenclature of the listed taxa. Sampling campaigns contributed to 116 new records of Basidiomycota for the Azores archipelago. In addition, there were new records for eight islands: 162 species found for the first time on São Miguel Island, 55 species new to Santa Maria Island, 33 species new to Flores Island, 15 species new to Terceira Island, 9 species new to Pico Island, 17 species new to São Jorge Island, 4 species new to Graciosa Island, and 2 species new to Corvo Island. The transformation of vegetation cover in the archipelago has been very drastic, and this is reflected in the presence of many foreign fungal species on the islands. From these data, we conclude that within Macaronesia, the diversity of Basidiomycota in the Azores is more similar to that in Madeira than in the Canary Islands.